The Predictive Validity of Teachers' Personality, Cognitive and Academic Abilities at the End of High School on Instructional Quality in Germany: A Longitudinal Study - Janina Roloff; Uta Klusmann; Oliver Lüdtke; Ulrich Trautwein (SAGE Publishing, 2020)
The present study investigated to what degree teachers' personality traits, cognitive abilities, and academic abilities (high school GPA), which were assessed at the end of high school as well as grades from the first and second state examinations of teacher education, predict later instructional quality. The study combined ratings of instructional quality from 3,768 German secondary school students and their 113 teachers with up to 10 years between assessment of teachers' personality traits, cognitive abilities, as well as academic abilities at the end of high school and student ratings of instructional quality. Multilevel regression analyses revealed that agreeableness, high school GPA, and the second state examination grade predicted teachers' instructional quality.